Cathodoluminescence study of Mg activation in non-polar and semi-polar faces of undoped/Mg-doped GaN core–shell nanorods. (8th February 2016) - Hortelano, V; Martínez, O; Cuscó, R; Artús, L; Jiménez, J
Abstract: Spectrally and spatially resolved cathodoluminescence (CL) measurements were carried out at 80 K on undoped/Mg-doped GaN core–shell nanorods grown by selective area growth metalorganic vapor phase epitaxy in order to investigate locally the optical activity of the Mg dopants. A study of the luminescence emission distribution over the different regions of the nanorods is presented. We have investigated the CL fingerprints of the Mg incorporation into the non-polar lateral prismatic facets and the semi-polar facets of the pyramidal tips. The amount of Mg incorporation/activation was varied by using several Mg/Ga flow ratios and post-growth annealing treatment. For lower Mg/Ga flow ratios, the annealed nanorods clearly display a donor–acceptor pair band emission peaking at 3.26–3.27 eV and up to 4 LO phonon replicas, which can be considered as a reliable indicator of effective p-type Mg doping in the nanorod shell. For higher Mg/Ga flow ratios, a substantial enhancement of the yellow luminescence emission as well as several emission subbands are observed, which suggests an increase of disorder and the presence of defects as a consequence of the excess Mg doping.